Development of a new fluorescence ratiometric switch for endogenous hypochlorite detection in monocytes of diabetic subjects by dye release method - Das, Sangita; Aich, Krishnendu; Patra, Lakshman; Ghoshal, Kakali; Gharami, Saswati; Bhattacharyya, Maitree; Mondal, Tapan Kumar (Tetrahedron letters, 2018)
A new quinoline-diaminomaleonitrile based probe was synthesised for the selective and ratiometric endogenous screening of OCl− in living diabetic blood cells. [Display omitted] •A new quinoline based probe has been designed for selective detection of OCl−.•The probe (HQMN) can detect OC− with a fast response time (within 100 s).•HQMN can detect endogenous OCl− in human monocytes.•HQMN can be used to track OCl− in living cells to identify the diabetic conditions. Increased oxidative stress in metabolic complications like type 2 diabetes, dyslipidemia and cardiovascular disorders exerts potential health hazards in many facets. Enhanced production of reactive oxygen species (ROS) due to increased oxidative stress promotes the damage of many biologically important macromolecules. Hypochlorous acid (HOCl), a microbicidal agent is also known to be an important ROS sub-species. An enhanced generation of endogenous HOCl due to diseased condition therefore can be detrimental to health. In present work, a new quinoline-diaminomaleonitrile based probe (HQMN) has been designed for the selective detection of hypochlorite. The probe in hand shows a selective ratiometric emission change towards OCl−. The probe behaves as a highly selective and sensitive tool for the detection of OCl− over other analytes with a fast response time (within 100 s). Bioimaging study revealed that HQMN can detect endogenous OCl− in human monocytes and an increase in endogenous HOCl concentration has been witnessed in diabetic condition compared to healthy control. Thus HQMN can be used as an excellent fluorescent probe for dynamic tracking of hypochorite in living biological cells especially to identify diabetic conditions.